2009
DOI: 10.1111/j.1095-8339.2009.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular appraisal ofBuniumand some related arid and subarid geophilic Apiaceae-Apioideae taxa of the Ancient Mediterranean

Abstract: Bunium is unusual in Apiaceae in having a variable cotyledon number and broad infrageneric dysploidy. To test the monophyly of the genus, phylogenetic relationships among 39 Bunium species were investigated with DNA sequence data from nuclear (nrITS) and plastid (psbA-trnH intergenic spacer) regions. Several other taxa with a similar ecology and geography were also included in the analyses. Our results suggest that Bunium is not monophyletic. Bunium spp. in the eastern part of the study area are more closely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 58 publications
(82 reference statements)
2
21
1
2
Order By: Relevance
“…this confirms in a much more detailed way the preliminary findings in previous molecular phylogenetic analyses including members of Carum (Papini 2006, Degtjareva & al. 2009).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…this confirms in a much more detailed way the preliminary findings in previous molecular phylogenetic analyses including members of Carum (Papini 2006, Degtjareva & al. 2009).…”
Section: Discussionsupporting
confidence: 90%
“…c. B. clarke) had been demonstrated to be morphologically alien to Carum; of these C. diversifolium was shown to be member of Trachyspermum link. also molecular phylogenetic studies by Papini (2006), and Degtjareva & al. (2009) indicated that Carum is polyphyletic, although their samplings usually included only few species of the genus.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…ETS sequences were generated for 45 of these same accessions (data for Postiella capillifolia could not be obtained despite repeated attempts). PsbA-trnH sequences for 10 species were also newly generated for this study and added to a matrix containing 36 previously published sequences (Degtjareva et al, 2009). Physospermum cornubiense (L.) DC.…”
Section: Molecular Studymentioning
confidence: 99%
“…Род Elwendia восстановлен как самостоятель-ный по отношению к Bunium L. с использовани-ем анатомо-морфологического, ботанико-геогра-фического и кариологического методов исследо-вания (Vasil'eva et al, 1985;Kljuykov, 1988), а также анализа молекулярных данных (Degtjareva et al, 2009(Degtjareva et al, , 2013. От рода Bunium он отличается широкой комиссурой плода, двусемядольными (но не односемядольными) проростками, геогра-фическим распространением и хромосомными числами.…”
unclassified